Research on Establishing a Foot Sizing System for Women with Diabetes as a Basis for Shoe Design - Bui, Van Huan (JST: Engineering And Technology For Sustainable Development, 2024)
Diabetic patients often suffer from foot diseases, in which foot ulcers are a dangerous complication and lead to the risk of amputation. Therapeutic shoes are well-fitting (highly comfortable) shoes that play an important role in reducing the risk of foot ulcers. Therefore, diabetics need to use therapeutic shoes, which are designed based on the patient's foot measurements. This article presents the results of research on establishing a foot size system based on measurements of 221 female diabetic patients at Khoai Chau District Medical Center, Hung Yen Province and at National hospital of Endocrinology. As a result, a foot size system based on the French size system has been built. The size system includes 5 sizes by foot length: 218, 224.5, 231, 237.5 and 244 mm. Each size of foot length has 5 sizes of its width (fullness). This size system accommodates more than 92.6% of the feet of women with diabetes. The research results are the basis for designing shoes to meet the usage requirements for Vietnamese women with diabetes.